If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3v + w + 8 + -2v + 2 = 0 Reorder the terms: 8 + 2 + 3v + -2v + w = 0 Combine like terms: 8 + 2 = 10 10 + 3v + -2v + w = 0 Combine like terms: 3v + -2v = 1v 10 + 1v + w = 0 Solving 10 + 1v + w = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + 1v + -10 + w = 0 + -10 Reorder the terms: 10 + -10 + 1v + w = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 1v + w = 0 + -10 1v + w = 0 + -10 Combine like terms: 0 + -10 = -10 1v + w = -10 Add '-1w' to each side of the equation. 1v + w + -1w = -10 + -1w Combine like terms: w + -1w = 0 1v + 0 = -10 + -1w 1v = -10 + -1w Divide each side by '1'. v = -10 + -1w Simplifying v = -10 + -1w
| -2-17-22=2y+3(y-6) | | -5+(19)+(-34)+44= | | 2x+5x^4+6=0 | | 8(4x+4)= | | -6(x+3)+2x+6=8x+7 | | 20*7-4*7= | | -16t^2+144t-160=0 | | 15w+21=3(5w-7) | | -5+200=100 | | 3y^2-6y-24= | | -3+3(z-2)=(-7z+3)-6 | | 3x=cos(0.5x) | | 18=6v | | 4u-7u=-1-14 | | 5(-3-6n)=195 | | 4x^2-4x-48= | | (x+4)(xy-6)=7x | | 16x^2+-40x+25=0 | | 5/2*4-10/5+6= | | 16x-40x+25=0 | | 5x^3-20x= | | -3y+2x-10y-5x+2y= | | 2(3ab+4bc+-2x)*x+-3x(2ab+-5cb+-4x+2)=0 | | 2f*f*3f= | | (7x^2-6x+29)+(2x^2+9x-72)= | | -3x+3y=18 | | 16/2*4-10/5+6= | | 6-17=-7y-4y | | 3x-4+5x=10x-(3+2x) | | 7+18=6u-u | | v^2-2v-3= | | 40=-7(t+1) |